Electrolyte additive, electrolyte and lithium secondary battery
By using electrolyte additives with multiple isocyanate groups in lithium-ion batteries to form a stable interface film, the problem of insufficient performance of lithium-ion batteries in high voltage and wide temperature ranges is solved, and better circulation, storage and low temperature performance is achieved.
Patent Information
- Application Number
- CN202210924884.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-08-03
AI Technical Summary
Existing lithium-ion batteries show insufficient performance in circulation, storage and other performance under high voltage and wide temperature ranges, especially under low temperature conditions.
An electrolyte additive is used, which consists of a compound with three or four isocyanate groups. By forming a stable interface film on the surface of the positive electrode and the negative electrode, the electrolyte decomposition is inhibited and the Li+ transmission capacity is improved, thereby improving the circulation and storage performance of the battery under different temperature conditions.
It significantly improves the cycle performance, storage performance and low-temperature discharge performance of lithium-ion batteries in high voltage and wide temperature ranges, and extends the service life of the battery.
Smart Images

Figure CN115189028B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte additive, an electrolyte and a lithium secondary battery. Background Art
[0002] As the world's energy demand continues to grow, the consumption rate of fossil energy on the earth continues to accelerate, which has brought increasingly prominent environmental problems. Efficient, clean, safe and renewable new energy and related technical fields have become a hot topic of research in countries around the world. Lithium-ion batteries have the advantages of high energy density, high discharge voltage, long cycle life, and easy maintenance, and have firmly occupied most of the market share in the field of mobile electronic devices.
[0003] Increasing the working voltage can increase the energy density of lithium-ion batteries. Conventional lithium-ion electrolytes are prone to oxidation reactions on the surface of the positive electrode material when the voltage is higher than 4.2V, resulting in a rapid decrease in the comprehensive performance of high-voltage batteries, especially the high-temperature performance. Moreover, the use of batteries is significantly limited by the operating temperature range. The operating temperature of consumer electronic devices is usually -20℃-60℃, which is basically consistent with the extreme operating temperature of conventional lithium-ion batteries; however, in order to adapt to regional and seasonal temperature differences, the power supply of future electric vehicles (EV) / hybrid electric vehicles (HEV) usually needs to work in the temperature range of -30-70℃ for a long time; aerospace / military equipment requires stronger adaptability, requiring the battery system to have a wider operating temperature range, especially the low temperature limit is extended to below -50℃, which puts forward higher requirements on low temperature performance than civilian products. The optimized design of the electrolyte system has become the most feasible and economical way to broaden the operating temperature range of lithium-ion batteries at this stage. Therefore, high-voltage wide-temperature lithium-ion battery electrolytes have become one of the hot spots in research and development.
[0004] At present, adding linear isocyanate organic compounds is one of the most effective ways to solve the above problems. The above isocyanate can form a thin and stable film on the positive electrode, and can effectively inhibit the generation of HF. It has been proven that it can improve the room temperature and high temperature cycle performance, high temperature storage and low temperature discharge performance of high voltage lithium-ion batteries. In the research and patents of linear isocyanate additives, the focus is mainly on those containing one isocyanate group and two isocyanate groups.
[0005] For example, CN201911215997.1 discloses a high-temperature lithium secondary battery electrolyte and battery. The high-temperature lithium secondary battery of the present invention comprises an additive composition composed of a diisocyanate compound and a bicyclic sulfate compound. When the composition is used together, it forms a flexible, thin and uniform SEI film on the negative electrode surface of the lithium secondary battery through synergistic effect, and passivates the positive electrode surface, inhibits the gas generation during the high-temperature storage of the lithium secondary battery, improves the high-temperature cycle performance and high-temperature storage performance, and increases the cycle life;
[0006] It discloses the following structural formula:
[0007] O=C=NR 1 -N=C=O;
[0008] CN202110197027.4 discloses the use of a compound as an electrolyte additive, and the structural formula of the additive is as follows:
[0009]
[0010] It is disclosed that the effect of using the above structure is better than that of dinitrile additives, and its storage performance and cycle performance at room temperature and high temperature are optimized.
[0011] Therefore, it can be concluded that the above structure combined with functional groups has the possibility of improving the performance of the electrolyte.
[0012] The technical problem to be solved in this case is: how to improve the high and low temperature circulation, storage and other performances of the electrolyte. Summary of the invention
[0013] One of the objects of the present invention is to provide an electrolyte additive for lithium ion battery electrolyte having good cycle performance at high voltage as well as high temperature storage and low temperature performance.
[0014] The second object of the present invention is to provide an electrolyte for lithium ion batteries containing the above electrolyte additive, which has good cycle performance at high voltage and high temperature storage and low temperature performance.
[0015] The third object of the present invention is to provide a lithium ion battery containing the above electrolyte, which has good cycle performance at high voltage and high temperature storage and low temperature performance.
[0016] To achieve the above object, the present invention provides an electrolyte additive, comprising a compound having a structure as shown in structural formula I:
[0017]
[0018] Among them, A 1A is independently selected from C1-20 alkylene or halogenated alkylene, C2-20 alkenylene or halogenated alkenylene; 2 , A 3 , A 4 , A 5 Each is independently selected from C1-20 alkyleneoxy or halogenated alkyleneoxy, C2-20 alkenyleneoxy or halogenated alkenyleneoxy; R is selected from isocyanate, C1-20 alkyleneoxy or halogenated alkyleneoxy, C2-20 alkenyleneoxy or halogenated alkenyleneoxy.
[0019] In the above electrolyte additive, the structural formula (I) is any one or more combinations of the following:
[0020]
[0021] At the same time, the present invention also provides an electrolyte, comprising a lithium salt, a solvent and an electrolyte additive, wherein the electrolyte additive is the electrolyte additive as described above.
[0022] In the above electrolyte, the mass of the electrolyte additive accounts for 0.1%-5.0% of the total mass of the electrolyte.
[0023] In the above electrolyte, the lithium salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(fluorosulfonyl)imide salt, and lithium bis(trifluoromethyl)sulfonyl imide.
[0024] In the above electrolyte, the concentration of the lithium salt in the electrolyte is 0.5M to 1.5M.
[0025] In the above electrolyte, the solvent is selected from one or more of chain carbonate solvents, cyclic carbonate solvents, and carboxylate solvents;
[0026] The cyclic carbonate solvent is one or more of ethylene carbonate, fluoroethylene carbonate, and propylene carbonate;
[0027] The chain carbonate solvent is one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate;
[0028] The carboxylate solvent is one or more of propyl acetate, ethyl acetate and propyl propionate.
[0029] The above electrolyte further comprises an auxiliary additive, wherein the auxiliary additive is at least one of vinylene carbonate and vinyl sulfate, and the amount of the auxiliary additive is 0.1wt%-5.0wt%.
[0030] Finally, the present invention also discloses a lithium secondary battery, which comprises a positive electrode, a negative electrode and an electrolyte as described in any one of the above items;
[0031] Wherein: the positive electrode material is selected from lithium transition metal oxides;
[0032] The lithium transition metal oxide is LiCoO 2 、LiMn 2 O 4 、LiMnO 2 , Li 2 MnO 4 、LiFePO 4 , Li 1+a Mn 1- x M x O 2 、LiCo 1-x M x O 2 、LiFe 1-x M x PO 4 or Li 2 Mn 1-x O 4 ;
[0033] M is one or more selected from Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, F, 0≤a<0.2, 0≤x<1;
[0034] The negative electrode material is selected from at least one of graphite, silicon-carbon composite material and lithium titanate.
[0035] Compared with the prior art, since the electrolyte additive of the present invention contains three or four isocyanate groups, it has more isocyanate groups than the commonly used one isocyanate group additive methyl isocyanate (MIN) and two isocyanate group additive hexamethylene diisocyanate (HDI), so the interface film formed has better inhibition of decomposition of positive electrode interface electrolyte and better Li + The transmission capacity can better improve the stability of the electrode / electrolyte interface under different temperature conditions and the rate performance of the battery, thereby better achieving a balance between cycle performance and high and low temperature performance.
[0036] The structural formulas of MIN and HDI are as follows.
[0037] DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the embodiments, but it does not constitute any limitation to the present invention. Any limited number of modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.
[0039] In order to explain the technical content of the present invention in detail, further description is given below in conjunction with the implementation modes.
[0040] Embodiment 1
[0041] 1. Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC = 1:1:1, and 1 mol of lithium hexafluorophosphate (LiPF 6 ), after the lithium salt is completely dissolved, 1.0% of compound 1 is added.
[0042] 2. Preparation of positive electrode: LiNi 0.6 Co 0.2 Mn 0.2 O 2 , conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) are mixed evenly in a mass ratio of 97.5:1.5:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on the aluminum foil for current collector, and the coating amount is 324g / m 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and after slitting, dried at 85°C under vacuum conditions for 4 hours, and the tabs were welded to make lithium-ion battery positive electrodes that meet the requirements.
[0043] 3. Preparation of negative electrode sheet: artificial graphite and silicon are mixed in a mass ratio of 90:10, and then mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, mix them evenly, apply the mixed slurry on both sides of the copper foil, dry and roll to obtain the negative electrode sheet, and make a lithium-ion battery negative electrode sheet that meets the requirements.
[0044] 4. Preparation of lithium-ion batteries: The positive electrode sheet, negative electrode sheet and separator prepared according to the above process are stacked to form a lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm. The capacity is 1800 mAh. The battery is vacuum-baked at 85°C for 48 hours, and the above electrolyte is injected to complete the battery production.
[0045] Embodiments 2 to 8
[0046] The preparation of the electrolyte, the positive electrode sheet, the negative electrode sheet and the lithium-ion battery are consistent with those in Example 1, but the compounds therein are changed to compounds 2 to 8 respectively.
[0047] Embodiment 9
[0048] 1. Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC = 1:1:1, and 1 mol of lithium hexafluorophosphate (LiPF 6 ), after the lithium salt is completely dissolved, 1.0% of compound 1 is added.
[0049] 2. Preparation of positive electrode: LiCoO 2 , conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) are mixed evenly in a mass ratio of 97.5:1.5:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on the aluminum foil for current collector, and the coating amount is 316g / m 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and after slitting, dried at 85°C under vacuum conditions for 4 hours, and the tabs were welded to make lithium-ion battery positive electrodes that meet the requirements.
[0050] 3. Preparation of negative electrode sheet: artificial graphite and silicon are mixed in a mass ratio of 90:10, and then mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, mix them evenly, apply the mixed slurry on both sides of the copper foil, dry and roll to obtain the negative electrode sheet, and make a lithium-ion battery negative electrode sheet that meets the requirements.
[0051] 4. Preparation of lithium-ion batteries: The positive electrode sheet, negative electrode sheet and separator prepared according to the above process are stacked to form a lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm. The capacity is 2000 mAh. The battery is vacuum-baked at 85°C for 48 hours, and the above electrolyte is injected to complete the battery production.
[0052] Embodiments 10 to 16
[0053] The preparation of the electrolyte, the positive electrode sheet, the negative electrode sheet and the lithium-ion battery are consistent with those in Example 1, but the compounds therein are changed to compounds 2 to 8 respectively.
[0054] Embodiment 17
[0055] 1. Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC = 1:1:1, and 1 mol of lithium hexafluorophosphate (LiPF 6 ), after the lithium salt is completely dissolved, 0.7% of compound 8 and 0.3% of auxiliary additive vinylene carbonate are added.
[0056] 2. Preparation of positive electrode: LiNi 0.6 Co 0.2 Mn 0.2 O 2 , conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) are mixed evenly in a mass ratio of 97.5:1.5:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on the aluminum foil for current collector, and the coating amount is 324g / m 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and after slitting, dried at 85°C under vacuum conditions for 4 hours, and the tabs were welded to make lithium-ion battery positive electrodes that meet the requirements.
[0057] 3. Preparation of negative electrode sheet: artificial graphite and silicon are mixed in a mass ratio of 90:10, and then mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, mix them evenly, apply the mixed slurry on both sides of the copper foil, dry and roll to obtain the negative electrode sheet, and make a lithium-ion battery negative electrode sheet that meets the requirements.
[0058] 4. Preparation of lithium-ion batteries: The positive electrode sheet, negative electrode sheet and separator prepared according to the above process are stacked to form a lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm. The capacity is 1800 mAh. The battery is vacuum-baked at 85°C for 48 hours, and the above electrolyte is injected to complete the battery production.
[0059] Embodiment 18
[0060] The method is substantially the same as the seventeenth embodiment, except that the auxiliary additive is vinyl sulfate.
[0061] Embodiment 19
[0062] 1. Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC = 1:1:1, and 1 mol of lithium hexafluorophosphate (LiPF 6 ), after the lithium salt is completely dissolved, 0.7% of compound 8 and 0.3% of auxiliary additive vinylene carbonate are added.
[0063] 2. Preparation of positive electrode: LiCoO 2 , conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) are mixed evenly in a mass ratio of 97.5:1.5:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on the aluminum foil for current collector, and the coating amount is 316g / m 2, dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and after slitting, dried at 85°C under vacuum conditions for 4 hours, and the tabs were welded to make lithium-ion battery positive electrodes that meet the requirements.
[0064] 3. Preparation of negative electrode sheet: artificial graphite and silicon are mixed in a mass ratio of 90:10, and then mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, mix them evenly, apply the mixed slurry on both sides of the copper foil, dry and roll to obtain the negative electrode sheet, and make a lithium-ion battery negative electrode sheet that meets the requirements.
[0065] 4. Preparation of lithium-ion batteries: The positive electrode sheet, negative electrode sheet and separator prepared according to the above process are stacked to form a lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm, and a length of 60 mm. The capacity is 2000 mAh. The battery is vacuum-baked at 85°C for 48 hours, and the above electrolyte is injected to complete the battery production.
[0066] Embodiment 20
[0067] The method is substantially the same as the nineteenth embodiment, except that the auxiliary additive is vinyl sulfate.
[0068] Comparative Examples 1 to 3, the electrolyte preparation method and the battery preparation method refer to Examples 1 to 8, and the additives are no additive, methyl isocyanate, and hexamethylene diisocyanate, respectively.
[0069] Comparative Examples 4 to 6, the electrolyte preparation method and the battery preparation method refer to Examples 10 to 16, and the additives are no additive, methyl isocyanate, and hexamethylene diisocyanate, respectively.
[0070] Table 1: Electrolyte compositions and battery systems of the embodiments and comparative examples
[0071]
[0072]
[0073]
[0074] Lithium-ion battery performance test
[0075] 25℃ 1.0C / 1.0C cycle test: Charge at 25℃ with 1.0C constant current to 4.5V, charge at 4.5V constant voltage to cut-off current 0.05C, then discharge at 1.0C constant current, discharge capacity is recorded as C 0 , repeat the charge and discharge steps for 1000 cycles, and obtain the 1000th cycle discharge capacity C 1000 , capacity retention rate = C1000 / C0*100%.
[0076] 45℃ 1.0C / 1.0C cycle test: Charge to 4.5V at 1.0C constant current at 45℃, charge to cut-off current 0.05C at constant voltage, then discharge the battery at 1.0C constant current, the discharge capacity is recorded as C 0 , repeat the charge and discharge steps for 1000 cycles, and obtain the 1000th cycle discharge capacity C 1000 , capacity retention rate = C 1000 / C 0 *100%.
[0077] Capacity retention test after 14 days storage at 60℃: Charge to 4.5V at 1.0C constant current at 25℃, charge to 0.05C at 4.5V constant voltage, then discharge the battery at 0.5C constant current, the discharge capacity is recorded as C0. At 25℃, charge to 4.5V at 1.0C constant current, charge to 0.05C at 4.5V constant voltage, then transfer the battery to 45℃ for 14 days, then discharge the battery at 1.0C constant current, the discharge capacity is recorded as C1, 14 days storage at 60℃ capacity retention = C 1 / C 0 *100%.
[0078] -20℃ low temperature discharge test: charge at 1.0C constant current to 4.5V at 25℃, charge at 4.5V constant voltage to cut-off current 0.05C, then discharge at 0.5C constant current, discharge capacity is recorded as C 0 At 25°C, charge the battery to 4.5V at 1.0C constant current, charge it to 0.05C at 4.5V constant voltage, then transfer the battery to -20°C and place it for 240min, then discharge it at 0.5C constant current, the discharge capacity is recorded as C 1 , -20℃ discharge rate = C 1 / C 0 *100%.
[0079] After the electrolyte in the above embodiment was made into a lithium ion battery, the normal temperature cycle performance, high temperature cycle performance and low temperature discharge performance of the lithium ion battery were tested. The results are shown in Table 2:
[0080] Table 2: Lithium-ion battery performance test results
[0081]
[0082]
[0083] After the battery was cycled at room temperature, it was disassembled and the nitrogen content on the positive and negative electrode surfaces was analyzed using an energy dispersive spectrometer (EDS) attached to a JSM-6510 scanning electron microscope (made in Japan). The analysis positions were 3 for each embodiment and comparative example. The nitrogen content can be used to determine the attachment of the active group N=C=O. The results are shown in Table 3:
[0084] Table 3: Nitrogen content of positive electrode in examples and comparative examples
[0085]
[0086]
[0087] Table 4: Nitrogen content of negative electrode in examples and comparative examples
[0088]
[0089]
[0090] in conclusion:
[0091] 1. By comparing Examples 1 to 8 and Examples 9 to 16, it is found that Compound 8 has the best room temperature and high temperature cycling, 60°C storage performance, and low temperature discharge performance. There are two possible reasons for this. First, the fluorine group and double bond group (non-initial carbon) will have a slight negative impact on battery performance; second, Compound 8 is a combination of 3 isocyanates with an unsaturated alkoxy group. The unsaturated bond at the beginning will make the additive film-forming performance better than that containing 4 isocyanates, and more isocyanate groups are deposited on the positive and negative electrode surfaces. In addition, Examples 1 to 8 and Examples 9 to 16 are superior to the comparative examples without additives, and the comparative examples containing methyl isocyanate and hexamethylene diisocyanate in terms of room temperature and high temperature cycling, high temperature storage, and low temperature discharge, whether in the NCM ternary system or the LCO lithium cobalt oxide system. Combined with the EDS data analysis, it can be seen that this shows that the additives containing three isocyanate and four isocyanate groups have a higher content of N-containing decomposition products on the positive electrode surface after film formation than methyl isocyanate and hexamethylene diisocyanate. Furthermore, the content of N-containing decomposition products in compound 8 in the example is higher than that of other compounds. It can be seen that the difference in electrochemical properties of different additives comes from the content of N-containing decomposition products in the positive and negative electrodes. The higher the content, the better the stability of the electrode / electrolyte interface and the battery performance. Therefore, the performance of the compound containing three isocyanates and one unsaturated alkoxy group is better in achieving both battery cycle performance and high and low temperature performance.
[0092] 2. Through Example 8, Example 17, Example 18, Example 16, Example 19, and Example 20, it can be found that the combination of the core additive and the auxiliary additives vinyl carbonate and vinyl sulfate of the present invention can further improve the performance. The auxiliary additive vinyl sulfate is more excellent than vinyl carbonate, indicating that the synergistic effect of cyclic sulfate and core additive is better than vinyl carbonate.
Claims
1. An electrolyte additive, characterized in that: The electrolyte additive is any one or more combinations of the following compounds 1 to 8; 2. An electrolyte comprising a lithium salt, a solvent and an electrolyte additive, characterized in that: The electrolyte additive is the electrolyte additive according to claim 1.
3. The electrolyte according to claim 2, characterized in that The mass of the electrolyte additive accounts for 0.1%-5.0% of the total mass of the electrolyte.
4. The electrolyte according to claim 2, characterized in that The lithium salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate)borate, lithium difluorooxalate)borate, lithium bis(fluorosulfonyl)imide salt, and lithium bis(trifluoromethyl)sulfonyl imide.
5. The electrolyte according to claim 4, characterized in that The concentration of the lithium salt in the electrolyte is 0.5M to 1.5M.
6. The electrolyte according to claim 2, characterized in that The solvent is selected from one or more of chain carbonate solvents, cyclic carbonate solvents, and carboxylate solvents; The cyclic carbonate solvent is one or more of ethylene carbonate, fluoroethylene carbonate, and propylene carbonate; The chain carbonate solvent is one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; The carboxylate solvent is one or more of propyl acetate, ethyl acetate and propyl propionate.
7. The electrolyte according to any one of claims 2 to 6, characterized in that: The invention also includes an auxiliary additive, which is at least one of vinylene carbonate and vinyl sulfate, and the amount of the auxiliary additive is 0.1wt%-5.0wt%.
8. A lithium secondary battery, characterized in that: The lithium secondary battery comprises a positive electrode, a negative electrode and the electrolyte according to any one of claims 2 to 7; Wherein: the positive electrode material is selected from lithium transition metal oxides; The lithium transition metal oxide is LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, Li 1+a Mn 1-x M x O2、LiCo 1-x M x O2、LiFe 1-x M x PO4 or Li2Mn 1-x O4; M is one or more selected from Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, F, 0≤a<0.2, 0≤x<1; The negative electrode material is selected from at least one of graphite, silicon-carbon composite material and lithium titanate.
Citation Information
Patent Citations
High-temperature lithium secondary battery electrolyte and battery
CN110931869A
A tetracyano-containing nitrile ether electrolyte additive, electrolyte, and lithium-ion battery
CN112768772B
Rechargeable electrochemical accumulator
CA2514783A1
High-voltage lithium cobalt oxide lithium ion battery non-aqueous electrolyte and lithium ion battery
CN111129586A